THE EFFECT OF USING GRAPHIC ORGANIZERS INNOVATION TO ORGANIZE MILLENNIAL COLLEGE STUDENTS’ IDEAS ON ENGLISH WRITING - M. Noor Sulaiman Syah (Universitas Islam Nahdlatul Ulama Jepara, 2018)
Organizing ideas was one of the crucial problems in the millennial era faced by the first grade English department students at IAIN Kudus in English writing. To encounter that problem, the observer (who was also the English writing lecturer) proposed the students to use the innovation of graphic organizers techniques to organize their ideas on English writing. For that reason, this study aimed to investigate the effectiveness of graphic organizers innovation in organizing students' ideas on English writing ability as well as their attitudes towards this essential language skill. The sample of this study was composed of 10 first semesters of English department students at STAIN Kudus during the academic year 2017-2018. This study (within subject design) was conducted in three phases. Two main sources were used to generate data for the study: (1) samples of students' English writing before and after the graphic organizers intervention, and (2) a writing attitude survey which was administered twice before and after intervention. The writing scores of the participants before and after the graphic organizers' intervention were compared and analyzed quantitatively using the test of significance to see if there were any distinctions between means of the scores. The data generated through the writing attitude survey was analyzed qualitatively to identify any changes in students' attitudes. The results of this study proved that the innovation of the graphic organizers techniques had significantly enhanced the millennial students' ability to organize ideas on English writing and had positively impacted their attitudes towards this skill. These results suggest that graphic organizers innovation can be an effective support in teaching writing for EFL learners.